2021
DOI: 10.1111/febs.16219
|View full text |Cite
|
Sign up to set email alerts
|

DDX3 interacts with USP9X and participates in deubiquitination of the anti‐apoptotic protein MCL1

Abstract: Here, we describe a novel interaction between the RNA helicase DDX3 and the deubiquitinase ubiquitin-specific peptidase 9 X-linked (USP9X) in human cells. Domain mapping studies reveal that the C-terminal region of DDX3 interacted with the N terminus of USP9X. USP9X was predominantly localized in the cytoplasm where the interaction between DDX3 and USP9X occurred. USP9X was not visibly enriched in cytoplasmic stress granules (SGs) under oxidative stress conditions, whereas overexpression of GFP-DDX3 induced SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…In a similar fashion to many other SG proteins, overexpression of DDX3X can trigger spontaneous SG formation ( Shih et al, 2012 ; Lai et al, 2021 ). Several disease-associated DDX3X mutations are more prone to triggering spontaneous SGs than wild-type DDX3X, and it is thought that this contributes to disease pathophysiology in medulloblastoma and neurodevelopmental delay (DDX3X syndrome) ( Valentin-Vega et al, 2016 ; Lennox et al, 2020 ).…”
Section: Translation Regulation By Ddx3x and Its Physiological Conseq...mentioning
confidence: 88%
See 2 more Smart Citations
“…In a similar fashion to many other SG proteins, overexpression of DDX3X can trigger spontaneous SG formation ( Shih et al, 2012 ; Lai et al, 2021 ). Several disease-associated DDX3X mutations are more prone to triggering spontaneous SGs than wild-type DDX3X, and it is thought that this contributes to disease pathophysiology in medulloblastoma and neurodevelopmental delay (DDX3X syndrome) ( Valentin-Vega et al, 2016 ; Lennox et al, 2020 ).…”
Section: Translation Regulation By Ddx3x and Its Physiological Conseq...mentioning
confidence: 88%
“…Conflicting reports also come from studies using 5′UTR luciferase reporter assays as read-outs of DDX3X-mediated translation regulation. Several studies found that DDX3X selectively regulated transcripts with highly structured 5′UTRs and did not affect translation efficiency of reporter mRNAs containing various unstructured 5′UTRs ( Soto-Rifo et al, 2012 ; Çelik et al, 2015 ; Lai et al, 2021 ). However, Geissler et al (2012) observed negative effects on translation of both structured and unstructured 5′UTR mRNA reporters upon DDX3X knockdown.…”
Section: Translation Regulation By Ddx3x and Its Physiological Conseq...mentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence from functional assays has demonstrated that USP9X acts as a vital modulator of cell apoptosis via direct or indirect regulation of the cell death‐related pathways including the extrinsic death receptor pathway and intrinsic mitochondrial pathway (Chen et al, 2021; Vucic et al, 2011). Multiple components such as c‐FLIP and ASK1 in the death receptor pathway, and MCL‐1 of the mitochondrial pathway are direct substrates for DUB USP9X (Kim et al, 2019; Lai et al, 2021; Nagai et al, 2009; Schwickart et al, 2010). Additionally, USP9X has an indirect impact on cell apoptosis via the cell death signaling pathways: for example, USP9X induces apoptosis in cholangiocarcinoma cells by increasing the expression of cleaved‐caspase3, a common effector of both the death receptor and the mitochondrial pathways through deubiquitination and preventing the degradation of EGLN3 (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…USP9X stabilizes MCL-1 through its interaction with the protein and the removal of the Lys48-linked polyubiquitin chains that mark a protein for proteasomal degradation ( 53 ). A recent study reported that the RNA helicase Asp-Glu-Ala-Asp-box polypeptide 3 interacted with the N-terminus of USP9X and participated in deubiquitination of MCL-1 ( 61 ). Therefore, human tumors with a high level of MCL-1 expression may be accompanied by the overexpression of USP9X ( 53 , 62 ).…”
Section: Cellular and Biological Functions Of Usp9xmentioning
confidence: 99%